2004
DOI: 10.1007/s00253-003-1421-5
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear thioredoxin peroxidase Dot5 in Saccharomyces cerevisiae : roles in oxidative stress response and disruption of telomeric silencing

Abstract: The DOT5 gene was originally cloned as one of the DOT (disrupter of telomeric silencing) genes; and later it was re-discovered as a nuclear thioredoxin peroxidase in Saccharomyces cerevisiae. Here, we demonstrate that the telomeric-silencing disruption activity of Dot5 is independent of thioredoxin peroxidase activity. In addition, Dot5 cannot suppress the increased susceptibility to peroxides of mutants defected in cytosolic thioredoxin peroxidase, even when Dot5 is expressed in the cytoplasm. Furthermore, Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In C. cinerea this gene shows a very strong induction in young fruiting body gills, whereas in other species no evidence for a transcript enrichment in gill tissues was found. Finally, we detected orthologs of S. cerevisiae Dot5 ( C. cinerea protein ID: 379600) (Table 39), a thioredoxin (thiol-specific peroxidase) that is involved in the detoxification of peroxides(Cha et al 2003; Izawa et al 2003), but was also reported to be involved in the regulation of telomere length. Thioredoxins, together with peroxiredoxins (thioredoxin peroxidase) make up the thioredoxin system, which acts similarly to the glutaredoxin system in ROS scavenging.…”
Section: Results: Developmentally Expressed Gene Classes In the Agari...mentioning
confidence: 99%
“…In C. cinerea this gene shows a very strong induction in young fruiting body gills, whereas in other species no evidence for a transcript enrichment in gill tissues was found. Finally, we detected orthologs of S. cerevisiae Dot5 ( C. cinerea protein ID: 379600) (Table 39), a thioredoxin (thiol-specific peroxidase) that is involved in the detoxification of peroxides(Cha et al 2003; Izawa et al 2003), but was also reported to be involved in the regulation of telomere length. Thioredoxins, together with peroxiredoxins (thioredoxin peroxidase) make up the thioredoxin system, which acts similarly to the glutaredoxin system in ROS scavenging.…”
Section: Results: Developmentally Expressed Gene Classes In the Agari...mentioning
confidence: 99%
“…The list was enriched for both single-stranded and double-stranded telomeric DNA binding proteins ( p = 2.1 × 10 –3 , 3.6 × 10 –3 ), nuclear proteins ( p = 3.0 × 10 –4 ) and chromosome-associated proteins ( p = 2.0 × 10 –3 ), all functions expected for this DNA locus based on its physiological role. Included on the list were several expected proteins, including Orc4 that binds to the ARS, 1 Sir4 involved in telomeric silencing, 25 and Cdc13, 26 Stm1, 27 Top1, 28 Dot5, 29 and Ebs1 30 that are all known to bind to the telomeres. We also identified over 20 other proteins that are involved in DNA and chromosome maintenance and nearly 50 other proteins that are known to localize to the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Dot5 (nTPx) is a nuclear 2-Cys Prx, which is most active against alkyl hydroperoxides (Cha et al 2003). However, it has been proposed to play a minor role as an antioxidant, predominantly functioning in telomeric silencing (Izawa et al 2004). Yeast Prx1 is a member of the 1-Cys family of Prx's and is active as a peroxidase (Pedrajas et al 2000).…”
Section: Antioxidant Defensesmentioning
confidence: 99%